The Progress of Eugenics - Field, James A. (Quarterly Journal of Economics, 1911)
I. The Beginnings of Eugenics. Plato, 2. — The Origin of Species and its influence, 3. — Galton and the modern eugenics movement, 4. — Hereditary Genius, 6. — Greg, 8. — Darwin, 10. — de Candolle, 12. — Galton's English Men of Science, 13. — Inquiries into Human Faculty, 15. — Natural Inheritance, 16. — The revival of eugenics. Karl Pearson, 17. — Galton's later writings, 19. — Eugenics: Its Definition, Scope, and Aims, 20. — II. Eugenic Investigations. Heredity, 24. — Pearson's biometric studies, 25. — The Francis Galton Laboratory for National Eugenics, 26. — The Eugenics Laboratory publications, 27. — The relative influence of heredity and environment, 29. — Criticism of the biometric method, 31. — Biometry v. Mendelism, 31. — Mendelian methods in eugenics, 33. — Early eugenic ideas in America, 33. — The American Breeders' Association, 35. — The Eugenics Record Office and its work, 36. — III. The Eugenic Program. The popularization of eugenics, 39. — The Eugenics Education Society, 39. — International organizations, 39. — Applied eugenics: Constructive v. restrictive methods, 41. — Attempts to restrict the increase of undesirables, 45. — IV. Recent eugenic literature. Saleeby's Parenthood and Race Culture, 47. — Whethams' The Family and the Nation, 48. — Kellicott's The Social Direction of Human Evolution, 51. — Davenport's Race Improvement through Eugenics, 53. — Eugenics in Europe, 57. — Rassenbiologie, 58. — The “Natur und Staat” series, 59. — V. The Rationale of Eugenics. The lack of an adequate social philosophy in prevalent eugenic opinion, 61. — Eugenics in relation to natural selection, 62. — Exceptional ability v. general betterment, 63. — The outlook for eugenics, 66.